2022
DOI: 10.3389/fevo.2022.983172
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence for phenological differences between non-native and native species

Abstract: Although many species shift their phenology with climate change, species vary significantly in the direction and magnitude of these responses (i.e., phenological sensitivity). Studies increasingly detect early phenology or high phenological sensitivity to climate in non-native species, which may favor non-native species over natives in warming climates. Yet relatively few studies explicitly compare phenological responses to climate between native vs. non-native species or between non-native populations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Studying the flowering patterns 23 related to climatic factors has been of interest to ecologists to interpret the behavior of non-native species. Similarly, regarding invasiveness, the timing of phenological traits can prove crucial since it enables introduced alien species to adapt to new environmental conditions 24 . Yet, few studies evaluate phenological responses to climate between native and non-native species 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Studying the flowering patterns 23 related to climatic factors has been of interest to ecologists to interpret the behavior of non-native species. Similarly, regarding invasiveness, the timing of phenological traits can prove crucial since it enables introduced alien species to adapt to new environmental conditions 24 . Yet, few studies evaluate phenological responses to climate between native and non-native species 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it has been suggested that non‐native species, invasive ones in particular, shift flowering time more than native species in response to warming and this can correlate with increases in abundance (Willis et al., 2010; Wolkovich et al., 2013; Zettlemoyer et al., 2019). If invasive species are more phenologically sensitive to climate than natives, this may allow them to better track changes in climate and reproduce at optimal times of the year, though high phenological sensitivity can be associated with increased risk and potentially lower reproductive fitness under certain conditions (Park et al., 2019; Park, Xie, et al., 2023; Xie et al., 2022; Zettlemoyer et al., 2021). Regardless, in this case, the degree of phenological similarity between native and invasive species will change.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, in this case, the degree of phenological similarity between native and invasive species will change. On the other hand, it has been demonstrated that both flowering phenology and its sensitivity to climate can be phylogenetically conserved (Davies et al., 2013; Park et al., 2022), and that shifts in the latter may not occur rapidly (Zettlemoyer et al., 2022). In this case, phenological synchrony among closely related species may remain relatively unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that competition may limit co-occurrence. Analogously, exotic plant species may invade a new community by exploiting early-season phenological niches in which competition by co-occurrence with native species is lower [96] (but see [97]). A similar pattern can be achieved through a consumer-resource dynamic: introduction of large vertebrate herbivores may have selected for advanced flowering time in forage species in the US Southwest because earlier flowering reduces herbivory-induced loss of reproductive structures [98].…”
Section: How Can Life-history and Demographic Theory Help Establish F...mentioning
confidence: 99%